NOTES ON MEXICAN DRUGS PLANTS AND FOODS III AHUAUHTLI THE MEXICAN CAVIAR - BACHSTEZ, MARCELO; ARAGON, ALTAGRACIA (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1973)
This completely documented monograph presents a review of the literature on the economic importance of the Simuliidae The external and internal morphology of the adult flies is thoroughly discussed The discussion of the bionomics of the adults includes
NATUR
Keywords: NOTES, MEXICAN DRUGS, PLANTS, FOODS III, AHUAUHTLI, MEXICAN CAVIAR; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL